Ganti Rugi Atas Gagal Panen Kolam Ikan Karena Kebocoran Limbah Tambang Emas Perspektif Fatwa MUI No. 22 Tahun 2011 Tentang Pertambangan Ramah Lingkungan di Desa Panyabungan Jae Kabupaten Mandailing Natal - Atikah Atikah; Rahmat Hidayat (LPPM Universitas Ekasakti Padang, 2023)
At the Panyabungan Jae gold mine location there was a waste leak, this waste leak caused losses due to fish pond harvest failure in the area. This research aims to find out the gold mine's compensation obligations for failed harvests in farmers' fish ponds. This research uses a qualitative method with an empirical juridical type of research, where the phenomenon to be studied is the phenomenon of crop failure caused by leakage of gold mining waste. Data was collected from observations and interviews with related parties, namely interviews with the mine and interviews with the pool owner. From the results of this research, it was found that in Islamic law, one party's mistake causes harm to the other party, so they have to fight. This is in accordance with what is explained in MUI Fatwa No. 22 of 2011 that gold mining business actors are obliged to offer to improve the environment and compensate for losses from fish pond harvest failures caused by waste leaks which result in losses for local residents in utilizing river flows. for irrigating rice fields and for daily needs, especially for fish pond farmers.